2007
DOI: 10.1211/jpp.59.3.0003
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, preparation and evaluation of flunarizine-loaded lipid microspheres

Abstract: The aim of this study was to investigate the feasibility of preparing flunarizine-loaded lipid microspheres. Lipid microspheres (LMs) are excellent drug carriers for drug delivery systems (DDS) and are relatively stable and easily mass-produced. They have no particular adverse effects. LMs have been widely studied as drug carriers for water-soluble drugs, lipid-soluble drugs and inadequately soluble (in water or in lipid) drugs, in that they have a lipid layer, a water layer and an emulsifier layer. Flunarizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Separately, based on the results, the absolute value of the zeta potential decreased markedly without adding 0.05% (w/v) sodium oleate. It has been reported that sodium oleate can increase the surface charge by forming an integral part of the emulsifier film, and consequently, increase the repulsion among LMs particles and help the physical stability of the formulation .…”
Section: Resultsmentioning
confidence: 99%
“…Separately, based on the results, the absolute value of the zeta potential decreased markedly without adding 0.05% (w/v) sodium oleate. It has been reported that sodium oleate can increase the surface charge by forming an integral part of the emulsifier film, and consequently, increase the repulsion among LMs particles and help the physical stability of the formulation .…”
Section: Resultsmentioning
confidence: 99%
“…Centrifugation was carried out in a CS120GXL ultracentrifuge (HITACHI Co. Japan) at 50 000 rpm for 1.5 h. The sample temperature was preset to 4 °C. Polyallomer tubes were used and their bottoms were pricked after centrifugation with a syringe needle to collect the aqueous phase 10. The amounts of B, C, and R in the aqueous phase were estimated by HPLC and the EEs were calculated by dividing the drug concentration in the dispersed phase by that in the whole emulsion.…”
Section: Methodsmentioning
confidence: 99%
“…A study was conducted to produce OA-SLN employing the film-ultrasound dispersion technique [ 108 ]. Another study aimed to produce OA-SLN using the film-ultrasonic wave dispersion technique.…”
Section: Challenges In Oa Deliverymentioning
confidence: 99%